Gross Motor Skills of Students with Autism Spectrum Disorder Aged 6-10 Years And Typically Developing Children on TGMD-2 - Pratama, Ezra; Kurniawan, Rama; Gamagitta, Laras Putri (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2024)
Gross motor skill (GMS) development is crucial for children with autism to increase independence in daily activities, physical fitness, and self-confidence. This study aims to quantitatively analyze the physical features based on GMS of autism spectrum disorder students aged 6-10. The method utilized in this study was a survey with a quantitative descriptive approach. The sampling technique is determined using purposive sampling based on specific considerations in the population. In this study, the total participants are 57 students, consisting of 14 students from SLB Autis Laboratorium UM and 43 from SDN 2 Sumbersari as supporting data. The test instrument operated in this study is the Test of Gross Motor Development-2 (TGMD-2), which assesses the gross motor skills of children aged 3-10 years in locomotor aspects and control objects. The research results on the physical features analysis of gross motor skills aged 6-10 years of autistic students at the SLB Autis Laboratorium UM obtained an inferior category. It impacts student development in daily activities, and consequently, teachers need to rearrange the design of learning programs for autistic students to improve gross motor skills. The teachers should evaluate the effectiveness of programs and interventions that have been implemented